Global subsoil organic carbon turnover times dominantly controlled by soil properties rather than climate - Zhongkui Luo; Guocheng Wang; Enli Wang (Nature Communications, 2019)
The sensitivity of soil organic carbon (SOC) in subsoil (below 0.3 m) to climate change is poorly constrained. Here, the authors map global subsoil (0.3–1 m soil layer) SOC turnover times and find that temperature and in general climate effects are secondary to effects due to soil properties at both local and global scales—this now needs to be regarded for diagnosing subsoil SOC dynamics.